RETRACTED ARTICLE: Association of milk consumption with the incidence of cholelithiasis disease in the US adult population - Feng Jia; Yu Ma; Yahui Liu (BMC, 2023)
Abstract Background Cholelithiasis is a common digestive system disease that imposes major burden on patients and society. Investigating the relationship between dietary factors and cholelithiasis risk can provide a basis for disease prevention. Previous studies on milk intake and cholelithiasis incidence have been limited.Therefore, the aim of our study was to assess the association between milk consumption and the incidence of cholelithiasis in males and females. Methods We selected 14,722 adults (≥ 18 years old) from National Center for Health Statistics (NHANSE) 2017-2020, and collected general characteristics of patients in the database, such as age, gender, race and body mass index (BMI), as well as dietary information (milk consumption). The occurrence of cholelithiasis was used as the outcome event, and the group was divided into cholelithiasis and non-cholelithiasis groups according to the outcome event. We used logistic regression models in generalized linear model (GLM) functions, controlling for demographic, lifestyle, and dietary factors, to estimate the association between milk intake and the incidence of cholelithiasis in males and females. Results A total of 14,722 adults were included. In the present study, the overall weighted prevalence of cholelithiasis was 10.96%, with 15.18% and 6.48% prevalence in females and males, respectively. Compared to infrequent milk intake, frequent milk intake (once a week or more) in females was associated with reduced cholelithiasis risk (OR 0.74, 95% CI 0.61-0.90). Daily milk intake in males was also related to lower cholelithiasis risk (OR 0.69-0.82). As adjusted variables increased in the models, predictive performance was improved (AUC 0.711 in females, 0.730 in males). Conclusions Appropriate milk intake may correlate with decreased cholelithiasis risk. Our study provides a basis for dietary interventions against gallstones, but prospective studies are needed to verify the results.